Walnut Shell-based Activated Carbon for Li—S Batteries and the Effect of Pore Structure on the Performance - Le WANG; Xianxian ZHOU; Liang CHEN; Yu LI; Donghong DUAN; Zhonglin ZHANG; Shibin LIU (Taiyuan Ligong Daxue xuebao, 2021)
Walnut shell (WS) was used as carbon source and KOH as activator. A series of activated carbon with different pore structures were produced by changing the mass ratio of KOH to carbonized precursor from walnut shell (KOH/carbonized precursor ratio), so as to reveal the relationship between the pore structure and the electrochemical performance. The result shows that the specific surface area, total pore volume, and percentage of mesoporous volume of activated carbon increased obviously with rising KOH/carbonized precursor ratio. Both the initial discharge specific capacity and the scaling performance of the composite cathode increased of first and then decreased slightly with the increase of specific surface area, total pore volume, and percentage of mesoporous volume. When the KOH/carbonized precursor ratio was 6∶1, WSAC-6/S with large specific surface area (3 913 m2/g), total pore volume (2.26 cm3/g), and percentage of mesoporous volume (59.4%) showed high initial specific capacity (1 397 mAh/g) and stable charge/discharge performance (869 mAh/g after 100 cycles at 0.2 C). Especially, at 0.5 C, it still exhibited excellent electrochemical performance, and the specific discharge capacity maintained at 707 mAh/g after 200 cycles.